Fenomena Cancel Culture Sebagai Kontrol Sosial pada Kasus KDRT Rizky Billar Terhadap Lesti Kejora - Effendi, Alfya Octovi Azzahra; Febriana, Poppy (Jurnal Riset Komunikasi (JURKOM), 2023)
The phenomenon of mass communication that is rife in this era is when social media is able to provide facilities for humans to be better known and insulted by many people. Data from a survey conducted by the We Are Social website states that as of January 2022 active users of social media in Indonesia have reached 191.4 million users. Social media has facilities as a medium of information that is packaged in the form of content. Public figures are one example of how someone uses social media well. A public figure must be careful in behaving because if he misbehaves, it can be fatal. Cancel culture is a new phenomenon in social media activities. it can be said that the cancel culture phenomenon plays a role in the process of social change where a certain view or rule is less acceptable to society. This study uses qualitative methods with narrative analysis. The results of the study show that the cancel culture practice in the Rizky Billiards case is in the form of cyberbullying which appears a lot on social media. Several cases were found on various social media such as Twitter to carry out career boycotts and exclusion. This ultimately had an impact on Rizky Billar's personal, family and career life. So that the practice of cancel culture that is carried out on public figures can be used as social control for other public figures.